Preoperative Stereotactic Radiosurgery for Brain Metastases - Routman, David M.; Yan, Elizabeth; Vora, Sujay; Peterson, Jennifer; Mahajan, Anita; Chaichana, Kaisorn L.; Laack, Nadia; Brown, Paul D.; Parney, Ian F.; Burns, Terry C.; Trifiletti, Daniel M. (Frontiers in Neurology, 2018)
Abstract Stereotactic radiosurgery (SRS) is increasingly utilized to treat the resection cavity following resection of brain metastases and recent randomized trials have confirmed postoperative SRS as a standard of care. Postoperative SRS for resected brain metastases improves local control compared to observation, while also preserving neurocognitive function in comparison to whole brain radiation therapy (WBRT). However, even with surgery and SRS, rates of local recurrence at one year may be as high as 40%, especially for larger cavities, and there is also a known risk of leptomeningeal disease after surgery. Additional treatment strategies are needed to improve control while maintaining or decreasing the toxicity profile associated with treatment. Preoperative SRS is discussed here as one such approach. Preoperative SRS allows for contouring of an intact metastasis, as opposed to an irregularly shaped surgical cavity in the post-op setting. Delivering SRS prior to surgery may also allow for a ‘sterilizing’ effect, with the potential to increase tumor control by decreasing intra-operative seeding of viable tumor cells beyond the treated cavity, and decreasing risk of leptomeningeal disease. Because there is no need to treat brain surrounding tumor in the preoperative setting, and since the majority of the high dose volume can then be resected at surgery, the rate of symptomatic radiation necrosis may also be reduced with preoperative SRS. In this mini review, we explore the potential benefits and risks of preoperative versus postoperative SRS for brain metastases as well as the existing literature to date, including published outcomes with preoperative SRS.